PEMANFAATAN LAHAN PEKARANGAN DENGAN MENERAPKAN KONSEP PEKARANGAN PANGAN LESTARI - Aulia, Lidiana; Wijaya, Wendi Rio; Karwati, Lilis; Hamdan, Ahmad (Jurnal Pengabdian Masyarakat Indonesia, 2024)
The utilization of yard land guided by the concept of sustainable food gardens is increasingly important for local food systems in the context of sustainability and food security. This extension aims to explain the utilization of yard land through the application of the concept of sustainable food gardens and evaluate its impact on food security and the environment. The method used was descriptive qualitative. The results showed that yard land has significant potential as a sustainable source of local food and contributes to community food security. The application of the sustainable food garden concept not only creates a sustainable local food source, but also encourages environmental sustainability and community involvement. It is concluded that the utilization of yard land by applying the concept of sustainable food gardens is carried out in a sustainable manner to encourage community initiatives, emphasizing the important role of individuals and families in supporting collective food security.